Water stress and ripeness effects on the volatile composition of Cabernet Sauvignon wines. (25th September 2017) - Talaverano, Inmaculada; Ubeda, Cristina; Cáceres‐Mella, Alejandro; Valdés, María Esperanza; Pastenes, Claudio; Peña‐Neira, Álvaro
Abstract: BACKGROUND: Controlled water deficits affect grape berry physiology and the resulting wines, with volatile composition being the one of the affected parameters. However, there is a potential disconnect between aromatic maturity and sugar accumulation. Accordingly, the effects of three different water status levels over two growing seasons (2014 and 2015) and two different harvest dates on the aroma compounds from Cabernet Sauvignon wines were studied. Volatile compounds were determined using headspace solid phase microextraction coupled with gas chromatoghraphy/mass spectrometry. RESULTS: Around 45 volatile compounds were determined in the wines and, among these, esters were affected the most, presenting lower concentrations when the most restrictive water treatment was applied in both years. By contrast, volatile acids presented the highest concentrations when the lowest level of irrigation was applied. On the other hand, a delay in harvesting produced an increase in the total amount of volatile compounds in samples from the most restrictive water treatment. These results are coincident with a principal component analysis that indicated a great separation between years, deficit irrigation treatments and harvest dates. CONCLUSION: The results of the present study suggest that a low water supply had a negative effect on the aromatic potential of wines at a similar ripening stage. However, this effect could be countered by harvesting at a later date. © 2017 Society of Chemical Industry